GROWTH, DEFAULT RISK, DAN PROFITABILITAS: PENGARUHNYA TERHADAP EARNINGS RESPONSE COEFFICIENT - Nurhuda, Nurhuda; Darmayanti, Yeasy (Jurnal Ilmiah Ekonomi Dan Bisnis, 2024)
This research aims to look at growth, default risk, and profitability (moderating variables), and their influence on the earnings response coefficient. The research used 35 banking companies as samples in the 2016-2020 observation year and used moderated regression analysis (MRA). The research results found that growth had a positive and significant effect on the earnings response coefficient and default risk had no effect on the earnings response coefficient. Placing profitability as a moderating variable is not able to moderate the relationship between growth and earnings response coefficient; However, profitability is able to moderate the relationship between default risk and earnings response coefficient in banking companies listed on the Indonesia Stock Exchange in 2016-2020.